Generative AI in Education: A Study of Undergraduate Students’ Expectations of ChatGPT - Paradeda, Raul Benites; Torres, Daniel Teodolino Barbosa; Takahashi, Adriana (RENOTE, 2025)
Abstract: This study investigated undergraduate students’ perceptions and expectations regarding using ChatGPT, a generative AI model, in their educational process. Two questionnaires were employed: one based on the Technology Acceptance Model, measuring perceived usefulness and ease of use; and another, with questions suggested by ChatGPT and validated through factor analysis, exploring specific concerns. The findings revealed that while 74% of participants had used ChatGPT, with 77% of users rating it as effective or very effective, they emphasized the importance of maintaining human interaction and diverse information sources in educational settings. Students expressed enthusiasm for ChatGPT’s potential to provide personalized support but also concerns about its reliability and ethical implications.